EVALUATION OF THE QUALITY OF MICROWAVE DEVICES IN RELATION TO ACTIVATION RESISTANCES - Kuzmenko, Oksana (Scientific Works of Vinnytsia National Technical University, 2015)
The paper illustrates simulation quality estimation in terms of reliability, validity and adequacy of the obtained results in order to determine the possibility of reliable application of the simulation procedure for designing microwave-range devices. REFERENCES 1. Кузьменко О. Н. Имитационное моделирование СВЧ-фильтров на основе экспериментальных данных / О. Н. Кузьменко, Г. А. Мирских // 22-я Международная Крымская конф. «СВЧ-техника и телекоммуникационные технологии». Севастополь 10-14 сентября 2012 г.: материалы конф. В 2 т. - Т. 1. Севастополь: Вебер, 2012 – C. 559 – 560. 2. Кузьменко О. Н. Имитационное моделирование СВЧ устройств, включенных в несогласованные тракты / О. Н. Кузьменко, Г. А. Мирских // 21-я Международная Крымская конф. «СВЧ-техника и телекоммуникационные технологии». Севастополь 12-16 сентября 2011 г.: материалы конф. В 2 т. - Т. 1. Севастополь: Вебер, 2011 – C. 440 – 441. 3. Кузьменко О. М. Вплив на характеристики частотно-вибіркових мікрохвильових пристроїв параметрів включення / О. М. Кузьменко, Г. О. Мірських // Вісник НТУУ «КПІ». Серія – Радіотехніка. Радіоапаратобудування. – 2012. – Вип. 49. – С. 129 – 135 4. Morin Dehah. Characterization and Modeling of SOI RF integrated components / Morin Dehah. – Universite catholique de louvain laboratoire d’hyperfrequences, 2003. – 212 p. 5. Вентцель Е. С. Теория вероятностей и ее инженерные приложения. Уч. пособие. / Е. С. Вентцель, Л. А. Овчаров. – М. : Высшая школа, 2000. – 480 с 6. Фельдштейн А. Л. Синтез четырехполюсников и восьмилюсников на СВЧ / А. Л. Фельдштейн, Л. Р. Явич. – М. : Связь, 1971. – 388 с. 7. Матей Д. Л. Фильтры СВЧ, согласующие цепи и цепи связи, т. 1 / Д. Л. Матей, Л. Янг, Е. М. Т. Джонс. – М. : Связь, 1971. – 439 с. 8. Marks R. B. A General Waveguide Circuit Theory / R. B. Marks, D. F. Williams // J. Res. Natl. Inst. Stan. – 1992. – Vol. 97. – P. 543 – 562. 9. Microwave measurements division, Jarvis Drive, Morgan Hill Arbitrary impedance Application Note [Електронний ресурс] // Режим доступу: http://downloadfile.anritsu.com/RefFiles/en-US/Services- Support/Downloads/Application-Notes/Application-Note/11410-00284B.pdf. 10. Dobrowolski Janusz A. Microwave network design using scattering matrix / Janusz A. Dobrowolski. – Artech house, 2010. - p. 269. 11. Kurokawa K. Power Waves and the Scattering Matrix / K. Kurokawa // IEEE Trans. Microwave Theory Tech. – 1965. – Vol. MTT-13, No. 2. – P. 194 – 202.